2013
DOI: 10.1111/capa.12015
|View full text |Cite
|
Sign up to set email alerts
|

La subsidiarité en droit européen et canadien : Une comparaison

Abstract: Sommaire Le principe de subsidiarité, l'un des principes les plus importants en droit européen, est récemment entré dans le débat constitutionnel canadien grâce à des décisions de la Cour suprême en matière de partage de compétences. Après un survol de l'histoire intellectuelle du principe en question, cet article compare la façon dont la subsidiarité a été traitée par la Cour suprême du Canada et par la Cour de justice de l'Union européenne, dans le but de discerner quelles leçons le Canada peut tirer de l'ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(1 citation statement)
references
References 15 publications
0
1
0
Order By: Relevance
“…Elinor Ostrom () looked at local systems and concluded that they can self organize in a sustainable manner. Ostrom's work is consistent with the OMC principle of subsidiarity — a concept favouring localized decision making and explored through its application in Canada by Erika Arban () in this issue. An interesting reflection of Ostrom's is that larger scale governance systems might either facilitate or destroy these more localized or focused systems.…”
Section: A Systems Approach To Learningmentioning
confidence: 73%
“…Elinor Ostrom () looked at local systems and concluded that they can self organize in a sustainable manner. Ostrom's work is consistent with the OMC principle of subsidiarity — a concept favouring localized decision making and explored through its application in Canada by Erika Arban () in this issue. An interesting reflection of Ostrom's is that larger scale governance systems might either facilitate or destroy these more localized or focused systems.…”
Section: A Systems Approach To Learningmentioning
confidence: 73%